Heavy Metal-Associated (HMA) Domain-Containing Proteins: Insight into Their Features and Roles in Bread Wheat (Triticum aestivum L.) - Mehak Taneja; Santosh Kumar Upadhyay (Biology)
The heavy metal-associated (HMA) domain-harboring proteins constitute critical players involved in the transport of various metal ions in plants, and are associated with development and stress responses. Herein, a total of 243 TaHMA genes were identified in the bread wheat genome, each of which had a characteristic molecular profile and a distinct chromosomal localization. The TaHMA proteins were distributed in five clades in phylogeny, which differed with respect to the distribution of the key HMA domain. Sub-cellular localization was variable for the TaHMA proteins. Gene structure analysis yielded similar results when compared with the orthologous counterparts. Cis-regulatory element analysis produced a range of promoter elements, suggesting their diverse biological roles. Gene duplication analysis revealed a crucial role played by tandem and segmental duplication events in the expansion of TaHMA genes. Synteny analysis highlighted the evolutionary relatedness of TaHMA genes with those derived from Arabidopsis and rice. Expression analysis provided crucial information about the role of TaHMAs in mediating vital responses in the plant body, including the development of tissues and the regulation of various abiotic stress conditions. Overall, the study provides significant cues and evidence to functionally annotate and characterize the differentially expressed TaHMAs in order to validate their role.